New tools to appraise udder morphology and milkability in dairy sheep - Marie-Etancelin C.; Aurel M.R.; Barillet F.; Jacquin M.; Pailler F.; Porte D.; Casu S.; Carta A.; Deiana S.; Tolu S. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
The aim of this paper was to estimate relevance of new tools to appraise traits related to dairy ewes milkability (udder morphology) and milk emission kinetics. Data were collected in two experimental flocks: a backcross population Sarda ï Lacaune and a purebreed Lacaune. The tools applied were: Two scoring tables developed in Italy and France, respectively, and digital picture analysis, for udder conformation; and an INRA automatic milk recording device for milk emission kinetics. High correlations between the two scoring tables as well as high average correlations between classifiers using the same table were estimated. Scored traits were repeatable within and between lactations. The udder picture analysis allowed the extraction of original and reliable measurements, confirmed by sufficient repeatabilities and showing good correlations with scores. Finally, data collected with electronic jars permitted the kinetics trait to be identified showing high repeatabilities (maximum milk flow and latency time) these traits outlining strong differences between the 2 experimental flocks.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)